Advertising as a method of forming cunsumer demands - Osadchyk, Oksana; Krainiuchenko (Fornolyak), Olga (My University, 2013)
The features of forming of consumer necessities on the basis of advertising and mechanism of influence of advertising are on the conduct of users.
Keywords: реклама; споживачі; потреби; попит; advertising; users; necessities; demand; кафедра маркетингу